Lifting the buzz out of provisioning pollination services- A review on role of forest management practices on pollination services - Krishnan, Smitha; Wiederkehr Guerra, Gabriela; Bertrand, Damien; Wertz, Sheila; Kettle, Christopher (2025)
Most flowering plants, including food crops and wild species, depend on animal pollinators, making them vital for maintaining biodiversity and continued food production. Pollinators thrive in diverse natural habitats that offer forage and nesting opportunities, particularly when plant production systems are limited. Effective landscape and forest management practices are essential to maintain pollinator populations, enhancing the resilience and productivity of forestry and agriculture. In this review, we present the effects of forest and landscape management practices on pollinators with 2 case studies, discuss measures for safeguarding pollinators and the key knowledge gaps that we need to address.